To reform and to procure: An analysis of the role of the state and the market in Indian agriculture - Kartik Misra; Deepankar Basu (University of Massachusetts, Department of Economics, 2022)
Since the early 2000s, many Indian states started reforming their agricultural marketing policies and allowed private traders to buy directly from farmers outside the state-regulated market system. The experience of these states during the period 2000 - 2012 can shed light on the impact of market-oriented reforms and the role of public procurement. Using individual-level National Sample Survey Data on agricultural wages and a new dataset on state-level average real farm income per cultivator for 18 major Indian states between 1987 - 2012, this paper shows, using both a difference-in-difference and a triple difference framework, that marketing reforms alone did not contribute to higher farm incomes and agricultural wages. However, when these reforms were coupled with public procurement at the minimum support price, farm incomes and agricultural wages significantly improved. The effects of public procurement were driven primarily by rice procurement. Our results suggest that market-reforms and public procurement at minimum support prices were complements which together contributed to raising rural incomes in states like Haryana, Madhya Pradesh, and Andhra Pradesh.
Keywords: O13; Q13; Q18; 330; farm incomes; agricultural wages; market-oriented reforms; public procurement; India